Risk Mitigation and Sustainability Status of The Seaweed Area for Food Sovereignty in Pasir Panjang, Kupang City, East Nusa Tenggara, Indonesia - Arianty, Devi; Aziz, Abdul; Usman, Lutfiah (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2025)
AbstractThe potential seaweed cultivation area at Pasir Panjang Beach in Kupang City, East Nusa Tenggara, Indonesia, faces various risks at every stage of its activities. This study aims to identify key risks, evaluate sustainability status, and formulate evidence-based mitigation strategies across five dimensions: production, post-harvest, economic, human resources, and institutional. Data were collected through field observations, water quality monitoring, interviews, and questionnaires distributed to 50 active farmer respondents and local experts. The Failure Mode and Effects Analysis method and Pareto diagram were used for risk analysis, Rapid Assessment Procedure - Rural Livelihoods (RAP-RL) for Multidimensional Scaling, leverage analysis to assess sustainability, and Monte Carlo simulation to measure the validity of the analysis results. The results indicate 30 risk drivers, with 16 priority risks consisting of 3 priority risks each in the post-harvest, institutional, and economic dimensions, three priority risks in the production dimension, and four priority risks in the human resources dimension. The highest sustainability index was in the human resources dimension (80.54), production (79.13), and economic (78.67), while post-harvest (33.76) and institutional (34.79) were classified as less sustainable. Mitigation strategies include using superior seeds, crop protection, farmer capacity building, institutional strengthening, and digital technology for the supply chain. Integrated interventions are needed to create an adaptive, resilient, and competitive seaweed cultivation system.Keywords: FMEA, food sovereignty, multidimensional scalling, Pareto, seaweedAbstrakKawasan potensial budidaya rumput laut di Pantai Pasir Panjang di Kota Kupang, Nusa Tenggara Timur, Indonesia menghadapi beragam risiko pada setiap tahapan kegiatan. Penelitian ini bertujuan mengidentifikasi risiko utama, mengevaluasi status keberlanjutan, dan merumuskan strategi mitigasi berbasis bukti pada lima dimensi: produksi, pasca panen, ekonomi, sumber daya manusia, dan kelembagaan. Data dikumpulkan melalui observasi lapangan, pengamatan kualitas air, wawancara dan penyebaran kuesioner pada 50 responden petani aktif dan pakar lokal. Metode Failure Mode and Effects Analysis dan diagram Pareto digunakan untuk analisis risiko, Rapid Assessment Procedure - Rural Livelihoods (RAP-RL) untuk Multidimensional Scaling, analisis leverage untuk menilai keberlanjutan, dan simulasi Monte Carlo untuk mengukur validitas hasil analisis. Hasil menunjukkan 30 penyebab risiko, dengan 16 risiko prioritas yang terdiri dimensi pasca panen, kelembagaan, dan ekonomi masing-masing 3 risiko prioritas, dimensi produksi 3 risiko priotas, dan dimensi sumber daya manusia 4 risiko prioritas. Indeks keberlanjutan tertinggi pada dimensi sumber daya manusia (80,54), produksi (79,13), dan ekonomi (78,67), sedangkan pasca panen (33,76) dan kelembagaan (34,79) tergolong kurang berkelanjutan. Strategi mitigasi mencakup penggunaan bibit unggul, pelindung tanaman, peningkatan kapasitas petani, penguatan kelembagaan, serta pemanfaatan teknologi digital untuk rantai pasok. Intervensi terintegrasi diperlukan guna menciptakan sistem budidaya rumput laut yang adaptif, resilien, dan berdaya saing.Kata kunci: rumput laut, keberlanjutan, risiko, multidimensional scaling, Pantai Pasir Panjang